The Pendulum Swings: Reconsidering Corporate Criminal Prosecution - Uhlmann, David M. (2016)
Corporate crime continues to occur at an alarming rate, yet disagreement persists among scholars and practitioners about the role of corporate criminal prosecution. Some argue that corporations should face criminal prosecution for their misconduct, while others would reserve criminal prosecution for individual corporate officials. Perhaps as a result of this conflict, there has been a dramatic increase over the last decade in the use of deferred prosecution and non-prosecution agreements for some corporate crimes, even as the government continues to bring criminal charges for other corporate crimes. To move beyond our erratic approach to corporate crime, we need a better understanding of what is accomplished by the criminal prosecution of corporations, a construct that considers retributive and utilitarian theories but also takes into account the expressive function of criminal law and the societal need for condemnation, accountability, and justice when crime occurs. In this article, I provide a justification for corporate criminal prosecution that identifies the moral content of corporate crime, considers the deterrent value of corporate prosecution, and explains why the expressive value of the criminal law is indispensable in the corporate context. Corporate wrongdoing has pernicious effects on our communities, the economy, and the environment, which warrant the condemnation the criminal law provides. Criminal prosecution of corporations upholds the rule of law, validates the choices of law-abiding companies, and promotes accountability. Together those values contribute to our sense that justice has been done when crime occurs, which enhances trust in the legal system, provides the opportunity for societal catharsis, and allows us to move forward in the aftermath of criminal activity. When corporations face no consequences for their criminal behavior, we minimize their lawlessness, and increase cynicism about the outsized influence of corporations